Protective Effects of Caesalpinia sappan Linn. and Its Bioactive Compounds on Cardiovascular Organs - Syamsunarno, Mas Rizky AA; Safitri, Ratu; Kamisah, Yusof (Frontiers in Pharmacology, 2021)
Cardiovascular diseases are the leading cause of death worldwide. The long-term aim of cardiovascular disease therapy is to reduce the mortality rate and decelerate the progression of cardiovascular organ damage. Current therapies focus on recovering heart function and reducing risk factors such as hyperglycemia and dyslipidemia. However, oxidative stress and inflammation are important causes of further damage to cardiovascular organs. Caesalpinia sappan Linn. (Fabaceae), a flowering tree native to tropical Asia, has antioxidant and anti-inflammatory properties. It is used as a natural dye to color food and beverages and as a traditional treatment for diarrhea, diabetes, and blood stasis. The phytochemical compounds in C. sappan, mainly the homoisoflavonoids brazilin, sappanone A, protosappanin, and hematoxylin, can potentially be used to protect cardiovascular organs. This review aims to provide updates on recent developments in research on C. sappan in relation to treatment of cardiovascular diseases. Many studies have reported protective effects of the plant’s bioactive compounds that reduce cardiac damage and enhance vasorelaxation. For example, brazilin and sappanone A have an impact on molecular and cellular changes in cardiovascular disease pathogenesis, mainly by modulating oxidative, inflammatory, and apoptotic signaling pathways. Therefore, bioactive compounds of C. sappan have the potential to be developed as therapeutic agents to combat cardiovascular diseases like myocardial infarction and vascular disease. This review could help further the understanding of the possible modulatory role of the compounds in cardiovascular diseases, thereby facilitating future studies.